Recursos didácticos en el proceso de enseñanza aprendizaje de Ciencias Naturales y la mejora del rendimiento académico de los estudiantes. Año Lectivo 2022-2023. - Coello Ruiz, Marlyn Nesty (2023)
The application of didactic resources, promote the participation and recreation of students during the teaching and learning process. This research was developed with the aim of << Enhance the academic performance of students, through the application of physic and technologic didactic resources, to the improvement of teaching and learning process of Natural Science, in ninth grade of basic education, of “Pio Jaramillo Alvarado” educative unit, academic year 2022 – 2023>>. Regarding the methodology for the research process, the inductive method was used, because it starts from the educative reality that students from nineth year have. In addition, insufficient participation of students in the classroom process, due to the scarce application of didactic resources, issue that turns into a low academic performance, on the other hand, the approach is qualitative, which allowed to characterize the before and after processes of the intervention. In the same way, this investigation is considered as participative action research (PAR) because, there is an interaction between the researcher and subjects of the research, with the aim of achieve a positive change according to the observed reality. According to its temporal location, it is transversal type because it is developed in a short period of time that include since diagnosis to intervention. Through the achieved results and through the application of evaluation instruments and research, it can be observed that the most significative didactic resources that facilitate the teaching and learning process are: the physics ones: interactive models, puzzles, flipcharts, informative posters; among technological resources: projector, slides, illustrations, music, etc. The use of didactic resources improved significantly the teaching and learning process of Natural Science, when motivating the active participation of students during the development of different topics, enhancing their academic performance, which it is evident in the grades achieved by them, before and after the intervention. Keywords: Academic performance, teaching-learning, student recreation, didactic resources.